A novel strategy for biomarker discovery: Neutral loss-dependent acquisition of circulating extracellular vesicles for the detection of phosphopeptides - Dong Wei; Hao Zhang; Mingyang Li; Liuxi Chu (Talanta Open)
Circulating extracellular vehicles (EVs) play a crucial role in intercellular communication by transporting a diverse array of biological signaling molecules. Growing evidence indicates that phosphoproteins within these EVs hold promise as biomarkers for diagnostic and prognostic assessments, particularly in oncology. In this study, EVtrap (extracellular vesicle total recovery and purification) was utilized to isolate urinary EVs. We then combined this with an advanced liquid chromatography-tandem mass spectrometry (LC−MS/MS) technique to perform neutral loss-information-dependent acquisition-enhanced product ion (NL-IDA-EPI) analysis. This technique is specifically tailored to quantify endogenous phosphopeptides in urinary EVs by monitoring a consistent mass loss of 49 Da (H3PO4, doubly charged state) in the MS2 spectra. In this study, over 2,000 putative phosphopeptide signals were detected in a 10-mL urine sample without the need for prior phosphopeptide enrichment, thus simplifying the process and potentially minimizing sample bias. Comparative analysis of samples from high- and low-risk prostate cancer patients and a healthy control group revealed six differentially expressed phosphopeptides. These phosphopeptides serve as a promising panel of potential biomarkers, highlighting the effectiveness of our analytical framework in tracking cancer-related signaling events via phosphorylation within EVs using NL-IDA-EPI.